Estimation of solubility parameter using small and fedors method for ionic liquids - Muhammad Ridhwan, Salman (2015)
Corrosion required three things to be formed such as water, iron and oxygen. The effect may harmful to pipeline equipment and also will cause operation and other maintenance issues. In the industry, different solvents are used in order to remove the present of iron oxide (Fe2O3) contaminants from pipeline. Thus, ionic liquids (ILs) as a solvent are used to study the solubility of Fe2O3 in removing if as contaminant from pipelines. Fedors’ and Small group contribution method are chosen applied as an estimation method in order to identify the suitable ILs. From the estimation method, 2-hydroxy-N-(2-hydroxyethyl)-N-methylethanolammonium acetate [HEME] Ac, 2-ethyl-N-(2-hydroxyethyl)-N-methylethanolammonium ethyl sulphate [HEME] ESO4, 1-ethyl-3-metylimidazolium ethyl sulphate [EMIM][ESO4] and 1-ethyl-3-methylimidazolium acetate, [EMIM] Ac were chosen and synthesized based on its solubility parameter. Each synthesized ILs will be tested by adding 0.0015g of Fe2O3 into 1.5mL ILs to observe their dissolution performance. From the observation, [HEME] Ac has reduced the amount of Fe2O3 better compared with other ILs. It can be concluded that low value of solubility parameter for both cation and anion can dissolve Fe2O3.